IMPLEMENTASI NILAI-NILAI PANCASILA SEBAGAI UPAYA PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR: KAJIAN PUSTAKA - Nyoman Sudirman, I; Pande Made Anggi Widiyanthi, Ni; Wayan Sintia, Ni; Ayu Made Tarisa Dewi, Sang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character building in elementary school students has become one of the primary concerns in education due to the various moral and social challenges in the modern era. One of the efforts to strengthen students' character is through the implementation of Pancasila values as the foundation of national life. This article aims to examine the implementation of Pancasila values as an effort to build the character of elementary school students through a literature review approach. The study employed a library research method with a descriptive qualitative approach. Data were collected from various sources, including books, scientific articles, journals, and relevant official documents, and were analyzed using content analysis by reviewing, comparing, and synthesizing information from the literature. The findings indicate that the implementation of Pancasila values can be carried out through integration into the learning process, teachers' role modeling, habituation of positive behavior in the school environment, and collaboration among schools, families, and communities. These efforts contribute to the development of students' religious, disciplined, honest, responsible, tolerant, caring, cooperative, and patriotic character. Therefore, the implementation of Pancasila values serves as an effective strategy for fostering students' character in accordance with the nation's noble values while supporting the realization of the Pancasila Student Profile.